2020
DOI: 10.2147/rmhp.s241265
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pharmacovigilance Perception and Knowledge Among Pharmacists and Interns in Saudi Arabia</p>

Abstract: The aim of this study was to determine and compare the level of knowledge and perception of ADRs reporting and pharmacovigilance among interns and hospital pharmacists in different health-care settings in Saudi Arabia. Methods: A cross-sectional study was conducted among pharmacists and pharmacy interns in different hospitals in Saudi Arabia. A total of 315 participants completed the self-administered and validated questionnaire during the period from August 2018 to March 2019. Results: There was poor percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…Around 71.3% of pharmacists reported an ADR during their practice, similar to the findings of studies from Oman (69.2%) ( Jose et al, 2014 ) and Makkah (70.9%) ( Al-Hazmi and Naylor, 2013 ). The results obtained in the current study are much higher than the outcomes reported in studies from Jizan (6.25%) ( Faqihi and Fageehi, 2019 ), Syria (10.8%) ( Bahnassi and Al-Harbi, 2018 ), Dammam (17.8%) ( Ali et al, 2018 ), Jordan (19.5%) ( Suyagh et al, 2015 ), and south India (22.8%) ( Gupta et al, 2015 ), Kuwait (26.8%) ( Alsaleh et al, 2017 ), a larger study carried out in Saudi Arabia (32.1%) ( Alshayban et al, 2020 ), Pakistan (32.4%) ( Hussain et al, 2021 ) and Majmaah (35.1%) ( Tadvi et al, 2018 ). Another noteworthy finding of our study is participants' positive attitude reflected in their practice, contrary to previous studies where poor reporting was reported despite positive attitudes ( Almandil, 2016 , Alsaleh et al, 2017 , Lemay et al, 2018 ).…”
Section: Resultscontrasting
confidence: 65%
See 2 more Smart Citations
“…Around 71.3% of pharmacists reported an ADR during their practice, similar to the findings of studies from Oman (69.2%) ( Jose et al, 2014 ) and Makkah (70.9%) ( Al-Hazmi and Naylor, 2013 ). The results obtained in the current study are much higher than the outcomes reported in studies from Jizan (6.25%) ( Faqihi and Fageehi, 2019 ), Syria (10.8%) ( Bahnassi and Al-Harbi, 2018 ), Dammam (17.8%) ( Ali et al, 2018 ), Jordan (19.5%) ( Suyagh et al, 2015 ), and south India (22.8%) ( Gupta et al, 2015 ), Kuwait (26.8%) ( Alsaleh et al, 2017 ), a larger study carried out in Saudi Arabia (32.1%) ( Alshayban et al, 2020 ), Pakistan (32.4%) ( Hussain et al, 2021 ) and Majmaah (35.1%) ( Tadvi et al, 2018 ). Another noteworthy finding of our study is participants' positive attitude reflected in their practice, contrary to previous studies where poor reporting was reported despite positive attitudes ( Almandil, 2016 , Alsaleh et al, 2017 , Lemay et al, 2018 ).…”
Section: Resultscontrasting
confidence: 65%
“…These results are similar to previously reported studies where 40% ( Faqihi and Fageehi, 2019 ), 43.4% ( Shamim et al, 2016 ) and 44.3% ( Almandil, 2016 ) had correctly identified the definition of PV, 66.3% ( Gupta et al, 2015 ) and 74.8% ( Alsaleh et al, 2017 ) knowing the purpose of PV activities. On the other hand, in other studies, a higher proportion of pharmacists at 81.08% ( Hussain et al, 2021 ) and 91% ( Alshayban et al, 2020 ) had rightly identified the definition of PV and 91.89% ( Hussain et al, 2021 ) identifying the purpose of PV. The definition of ADR was correctly identified as any noxious or undesired effect of a drug occurring at normal doses by 68.3%, reflecting the results of other studies ( Suyagh et al, 2015 , Bahnassi and Al Harbi, 2018 , Faqihi and Fageehi, 2019 ), while 22.8% defined an ADR wrongly as adverse health outcomes associated with inappropriate drug use.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…[17]. The provision of education and training programs on pharmacovigilance for pharmacist practice can increase pharmacist knowledge and foster good perceptions of pharmacovigilance and reporting of ADR [18]. The correlation test results between the knowledge and attitudes of pharmacists regarding pharmacovigilance obtained a significance value of 0,006 and a correlation coefficient value of 0,219.…”
Section: Advances In Health Sciences Research Volume 40mentioning
confidence: 99%
“…1 The terms "pharmacovigilance" are derived from the Greek words pharmakon (drug) and vigilare (vigilance) (monitor or keep an eye on). 2 Pharmacovigilance (PV) is described as "the science and techniques associated to the identification, assessment, understanding, and prevention of adverse effects or other drugrelated problems" by the World Health Organization (WHO). 3 PV evaluates a medicine's risk-benefit profile in order to improve patient safety.…”
Section: Introductionmentioning
confidence: 99%